The Effect of Platelet-Rich Plasma on Osseointegration Period of Dental Implants - Mahammed W Al-Gailani; Thair Abdul-Lateef (College of Dentistry/ University of Baghdad, 2015)
Background: The preparation of Platelet-rich plasma (PRP) is minimally invasive way, simple, low cost to obtain natural autologous growth factors and is now being widely used in different fields of medicine for its ability to increase the regeneration potential of tissue. The aim of this study was to investigate the effect of local application of autologous PRP gel on acceleration rate of osseointegration period by clinical assessment accomplished by determining the changes in implant stability during 3 months healing period using resonance frequency analysis (RFA). Materials and methods: A total of 28 dental implants were inserted in edentulous maxillae or mandibles of 13 patients using a split mouth design, i.e. each patient was received at least two dental implants at the same session, one implant was implanted in association with PRP which was placed locally in one site, to serve as PRP group, and the other implant was placed without PRP, to serve as a control group. Both groups were followed with repeated implant stability measurement by means of resonance frequency analysis at different time intervals (at the time of implant placement, 8th week, and 12th week postoperatively). Results: There was no obvious statistically significant difference in mean ISQ between PRP and control groups (P > 0.05) at baseline, 8 weeks, and 12 weeks postoperatively. Conclusions: Within the limitations of the present study, no appreciable clinical effect was observed to accelerate the rate of osseointegration of sandblasted acid-etched endosseous dental implants when using topical application of autologous PRP gel into the prepared drill holes.